Level of evidence analysis for the latest German national guideline on treatment of patients with severe and multiple injuries and ATLS - Münzberg, Matthias; Wölfl, Christoph Georg (World journal of surgery, 2015)
PurposeAdvanced Trauma Life Support (ATLS®) is one of the world’s best-known training programs for medical providers. Revisions of the ATLS manual have been evidence based for a number of years. In 2011, a level 3 (S3) evidence- and consensus-based guideline on the treatment of patients with severe and multiple injuries was published in Germany. The scope of this study was the systematic comparison of the educational content of the ATLS concept and the interdisciplinary “S3 polytrauma guideline.”Methods A total of 123 key recommendations of the guideline were compared with the content of the ATLS manual (9th edition). Depending on the level of agreement, the recommendations were classed in the following categories: (1) Agreement. (2) Minor variation. (3) Major variation.ResultsAn overall 86 % conformity was found between the key recommendations of the guideline and the ATLS® manual. The ATLS® primary survey (ABCDE) showed an 85 % conformity. The degree of conformity for the individual priorities was as follows: A (Airway) 79 %, B (Breathing) 79 %, C (Circulation) 86 %, D (Disability) 93 %, E (Exposure) 100 %. The ATLS® secondary survey showed a 94 % conformity. The main differences were in the areas of anesthetic induction, fluid administration, and coagulation therapy.ConclusionsAccording to our comparison, the educational content and manual of the ATLS are largely compatible with a high level of evidence S3 guideline. However, subsequent editions of both the ATLS® and the S3 guideline should re-examine and reassess a number of aspects.
Gesehen am 21.02.2017